Papaverine Infusion Through Aortic Root before Cardiac Self-recovery in Heart Valve Replacement with TiO2 Nanocrystalline Film Material: Heart Valve Replacement with TiO2 Nanocrystalline Film Material - Tan, Xiong; Li, Jinjie; Jin, Weitao; Mei, Bo; He, Guangjie; Wang, Yali; Wei, Shuliang; Lai, Yinglong (Cellular and Molecular Biology, 2022)
This work was to investigate TiO2 nanocrystalline film material in heart valve replacement (HVR) and the effect of papaverine infusion through the aortic root before cardiac self-recovery during the HVR. TiO2 nanocrystalline films were prepared by radio frequency (RF) reactive sputtering. The crystallization characteristics and surface morphology of TiO2 nanocrystalline films were observed by X-ray diffraction and scanning electron microscopy, and the anti-platelet adhesion and anti-coagulation properties of the films were analyzed. 86 patients with heart valve disease were selected and all underwent HVR. They were randomly divided into a control group (routine treatment) and an experimental group (papaverine perfusion through aortic root), with 43 cases in each group. The rate of cardiac self-recovery and the dosage of dopamine were observed. The results showed that the TiO2 nanocrystalline film was composed of a large number of uniform particles, and the average particle size was about 18.97 ± 7.28 nm. The rate of cardiac self-recovery in the experimental group was 97.67%, which was significantly higher than that in the control group (67.44%) (P< 0.05). The dosage of epinephrine, dopamine, and duration of cardiopulmonary bypass (CPB) assistance in the observation group were less than those in the control group (P < 0.05). These results indicated that TiO2 nanocrystalline film could be used in HVR, and papaverine infusion through aortic root before HVR and myocardial protection measures can significantly improve the rate of cardiac self-recovery and promote postoperative recovery.